Prion-mediated neurodegeneration is associated with early impairment of the ubiquitin–proteasome system - McKinnon, Chris (Acta Neuropathol, 2015)
Prion diseases are a group of fatal neurodegenerative disorders characterised by the accumulation of misfolded prion protein (PrP(Sc)) in the brain. The critical relationship between aberrant protein misfolding and neurotoxicity currently remains unclear. The accumulation of aggregation-prone proteins has been linked to impairment of the ubiquitin–proteasome system (UPS) in a variety of neurodegenerative disorders, including Alzheimer’s, Parkinson’s and Huntington’s diseases. As the principal route for protein degradation in mammalian cells, this could have profound detrimental effects on neuronal function and survival. Here, we determine the temporal onset of UPS dysfunction in prion-infected Ub(G76V)-GFP reporter mice, which express a ubiquitin fusion proteasome substrate to measure in vivo UPS activity. We show that the onset of UPS dysfunction correlates closely with PrP(Sc) deposition, preceding earliest behavioural deficits and neuronal loss. UPS impairment was accompanied by accumulation of polyubiquitinated substrates and found to affect both neuronal and astrocytic cell populations. In prion-infected CAD5 cells, we demonstrate that activation of the UPS by the small molecule inhibitor IU1 is sufficient to induce clearance of polyubiquitinated substrates and reduce misfolded PrP(Sc) load. Taken together, these results identify the UPS as a possible early mediator of prion pathogenesis and promising target for development of future therapeutics. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00401-015-1508-y) contains supplementary material, which is available to authorized users.